Successful Recanalization of the Superior Mesenteric Artery in Acute Mesenteric Ischemia - F. D. Kochetkov; R. E. Kalinin; I. A. Suchkov; A. O. Antonenko; O. V. Krymov; V. V. Khabibulin; M. I. Faber (Неотложная медицинская помощь, 2024)
The article describes a clinical case of recanalization of the superior mesenteric artery during acute mesenteric ischemia in an 81-year-old patient who was admitted to the emergency hospital in Ryazan with a clinic for “acute” abdomen. As a result of a diagnostic study, collection of anamnestic data and clinical picture, a diagnosis was made: “Embolism of mesenteric vessels.” Taking into account the early diagnosis (less than 4 hours from the onset of the disease), as well as the extremely complicated somatic status, selective angiography with mesentericography was performed, which revealed the patency of the main trunk of the superior mesenteric artery and complete occlusion of the distal segment of the intestine. Revascularization was performed ischemic area of the superior mesenteric artery. In the postoperative period, positive dynamics was observed, with complete relief of the clinical manifestations of mesenteric ischemia. On the 12th day, the patient was discharged for outpatient treatment under the supervision of a surgeon at her place of residence in satisfactory condition.